2017
DOI: 10.1111/jcpe.12663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of EMD liquid (Osteogain) on periodontal healing in class III furcation defects in monkeys

Abstract: Within their limits, the present data indicate that Osteogain possesses favourable physicochemical properties facilitating adsorption of amelogenin on ACS and may additionally enhance periodontal wound healing/regeneration when compared to Emdogain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 39 publications
1
30
0
2
Order By: Relevance
“…Interestingly, our group recently characterized the adsorption of enamel matrix proteins (namely amelogenins) to absorbable collagen sponges and found superior adsorption when compared to bone‐grafting materials (Miron et al, ). The combination of EMD‐liquid with an adsorbable collagen sponge was later shown to facilitate periodontal regeneration in a monkey animal model (Shirakata et al, ). These findings follow work with other recombinant growth factors such as bone morphogenetic proteins (BMPs) that routinely combine their growth factors with an absorbable collagen sponge for better growth factor adsorption and release (Coomes et al, ; De Sarkar et al, ; Spagnoli & Choi, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our group recently characterized the adsorption of enamel matrix proteins (namely amelogenins) to absorbable collagen sponges and found superior adsorption when compared to bone‐grafting materials (Miron et al, ). The combination of EMD‐liquid with an adsorbable collagen sponge was later shown to facilitate periodontal regeneration in a monkey animal model (Shirakata et al, ). These findings follow work with other recombinant growth factors such as bone morphogenetic proteins (BMPs) that routinely combine their growth factors with an absorbable collagen sponge for better growth factor adsorption and release (Coomes et al, ; De Sarkar et al, ; Spagnoli & Choi, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The results from that study demonstrated that markedly more EMD adsorption was observed closer to the bone‐grafting material surface when EMD‐liquid was utilized, with NBM demonstrating the most efficient loading and release of EMD over time (Miron et al, ). Furthermore, our research group recently conducted a large preclinical animal study in monkeys and demonstrated the ability for EMD‐liquid to more favorably and predictably improve periodontal regeneration in a furcation defects when compared to EMD‐gel (Shirakata et al, ). Nevertheless, its ability to stimulate bone formation in pure bone defects in a large animal model remains necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Further advantages of using EMD without its PGA carrier include more fluid consistency and subsequent improvement of surface coating and penetration of enamel matrix proteins (EMPs) within the bone biomaterials coupled with the capacity for a gradual release of EMPs with time . In addition, a liquid carrier system for EMD possesses favorable physicochemical properties that facilitate adsorption of amelogenin on an absorbable collagen sponge and may additionally enhance periodontal wound healing/regeneration compared with the liquid carrier system for EMD . From these results, the hydrophilic C‐terminus of amelogenin peptide may be effective for periodontal regeneration, similar to the liquid carrier system for EMD.…”
Section: Discussionmentioning
confidence: 99%
“…47 In addition, a liquid carrier system for EMD possesses favorable physicochemical properties that facilitate adsorption of amelogenin on an absorbable collagen sponge and may additionally enhance periodontal wound healing/regeneration compared with the liquid carrier system for EMD. 48,49 From these results, the hydrophilic C-terminus of amelogenin peptide may be effective for periodontal regeneration, similar to the liquid carrier system for EMD. Further animal studies are now necessary to evaluate the regenerative potential of AMG-CP in combination with MSCs in craniofacial defects.…”
Section: F I G U R E 4 Effects Of Lamp1 Blockade On the Enhancement Omentioning
confidence: 92%
“…This combination has recently been examined in a rodent bone femur defect model and has demonstrated favorable bone regenerative outcomes (Zhang et al, ). Further, EMD‐liquid absorbed in a collagen sponge has been shown to induce favorable periodontal regenerative outcomes in intrabony and furcation defects in monkeys (Shirakata, Miron, Nakamura, et al, ; Shirakata, Miron, Shinohara, et al, ). However, it remains unclear whether the combination of deproteinized bovine bone with EMD‐liquid as an adjunct, offers any additional benefit.…”
Section: Introductionmentioning
confidence: 99%